In-situ Synthesis and Properties of Porous Cobalt Sulfide Nanoneedle Bundles Arrays on Nickel Foam as Electrodes for Supercapacitors. Issue 5 (May 2018) - Peng, Sun; Jicai, Liang; Guangyi, Chen; Yuhui, Li; Kaiyuan, Zhou; Jiaang, Liu; Wenzhuo, Zhang; Fu, Niu; Wanxi, Zhang
Abstract: Freestanding porous Co9 S8 nanoneedle bundles arrays on Ni foam were in-situ synthesized by a facile ion exchange reaction and were directly used as the electrode for supercapacitors. The structure and morphology were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), and transmission electron microscope (TEM). Cyclic voltammetry (CV), chronopotentiometry (CP) and electrochemical impedance spectroscopy (EIS) were adopted to evaluate the electrochemical property of the porous Co9 S8 nanoneedle bundles arrays electrode in 3 mol/L KOH solution. The results show that the specific capacitance of the porous Co9 S8 nanoneedle bundles arrays is 1400 F·g -1 at a current density of 4 A·g -1 and the arrays exhibit good cycling stability. The excellent electrochemical performance can be ascribed to the porous nanostructure of Co9 S8 nanoneedle bundles arrays and the 3D conductive nickel foam, which can increase the contact areas between electrode and electrolyte and improve the conductivity of the whole electrode.